2020
DOI: 10.36460/kavaka/54/2020/38-42
|View full text |Cite
|
Sign up to set email alerts
|

New species and new records of Astrosphaeriellaceae from Andaman Islands, India

Abstract: Andaman and Nicobar Islands of India are relatively underexplored for fungal diversity. From the studies conducted from Andaman region, a few new species and new records have been documented.is characterized by superficial ascomata, or beneath the host periderm, thick carbonaceous walls with central ostioles, brown fusiform ascospores, hyphomycetous or ceolomycetous anarmophs. In the present paper, we introduce two new species, viz. and and report two new records i.e and .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The pairwise nucleotide comparison showed that our strain (CGMCC 3.23748) differs from L. urticae (MFLU 18-0591) in 44/487 bp of ITS (9.03%, with 5 gaps) and L. pedicularis (CBS 390.80) in 37/513 bp of ITS (7.23%, with 6 gaps) and 24/334 bp of tub 2 (7.19%, with 2 gaps). Significant morphological differences were observed when compared with the literature for the genus (for example, [ 2 , 5 , 13 , 41 , 53 ]). Leptosphaeria yunnanensis differs from related species by having a unique conidiomatal wall that occupies almost the entire interior of the conidiomata and sporulation indistinctly in the centre.…”
Section: Resultsmentioning
confidence: 96%
“…The pairwise nucleotide comparison showed that our strain (CGMCC 3.23748) differs from L. urticae (MFLU 18-0591) in 44/487 bp of ITS (9.03%, with 5 gaps) and L. pedicularis (CBS 390.80) in 37/513 bp of ITS (7.23%, with 6 gaps) and 24/334 bp of tub 2 (7.19%, with 2 gaps). Significant morphological differences were observed when compared with the literature for the genus (for example, [ 2 , 5 , 13 , 41 , 53 ]). Leptosphaeria yunnanensis differs from related species by having a unique conidiomatal wall that occupies almost the entire interior of the conidiomata and sporulation indistinctly in the centre.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, the remaining states, such as Arunachal Pradesh, Assam, Gujarat, Haryana, Madhya Pradesh, Mizoram, Nagaland, Sikkim, Tamil Nadu, Telangana, West Bengal, Tripura, as well as the Union Territories of Andaman and Nicobar Islands, have received significantly less attention in terms of research on this subject. Ao and Deb, 2019;Ao et al, 2016;Chuzho and Dkhar, 2017;Chuzho and Dkhar, 2018;Chuzho and Dkhar, 2019a;Dargan, 1976;Deb et al, 2008;Debnath et al, 2020;Dey et al, 2016;Li et al, 2015;Maharachchikumbura et al, 2016;Niranjan and Sarma, 2018;Patil et al, 2012;Paul, et al, and Dkhar, 2018;Chuzho and Dkhar, 2019a;Dargan, 1976;Deb et al, 2008;Debnath et al, 2018;Debnath et al, 2020;Dey et al, 2016;Li et al, 2015;Niranjan and Sarma, 2018;Patil et al, 2012;Paul et al,2019 Dargan, 1976;Deb et al, 2008;Debnath et al, 2018;Debnath et al, 2020;Niranjan and Sarma, 2018;Patil et al, 2012 Xylaria myosurus Mont.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Niranjan and Sarma [451] compiled a checklist of fungi reported from the Andaman-Nicobar Islands, where many palmicolous fungi have been documented. Several other palmicolous fungi, including new species, have been reported from the rainforests of these islands by Ram and Sinha [452] and Niranjan and Sarma [453][454][455][456][457].…”
Section: The Palmicolous Hyphomycetes From Central American Countriesmentioning
confidence: 91%
“…Later, the new species Dictyocheirospora indica (as Dictyosporium indicum) was collected on a petiole of Phoenix rupicola from India [593] and the new species Endophragmiella licualae was collected on dead branches of Licuala fordiana from China [594]. More recently, several palmicolous fungi, including new species, have been reported from the rainforests of the Andaman-Nicobar Islands (India) by Niranjan and Sarma [453][454][455]457] based on morphology alone, including important palmicolous genera whose taxonomic resolution highly relies on DNA sequence data, such as members of Aigialaceae, viz. Fissuroma and Neoastrosphaeriella, and Astrosphaeriellaceae, viz.…”
Section: Palmicolous "Anamorphs": a Plethora Of Botryosphaeriaceae An...mentioning
confidence: 99%